2014
DOI: 10.1089/chi.2013.0070
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Effects of a Tailored Web-Based Intervention on Promoting Fruit and Vegetable Intake in African American Families

Abstract: Background: The current study examined the effects of a Web-based tailored parenting intervention on increasing fruit and vegetable intake in African American families.Methods: Forty-seven African American parents (mean age, 41.32 -7.30; 93.6% female) with an adolescent (mean age, 13.32 -1.46; 59.6% female) participated in a Web-based autonomy-support parenting tailored intervention session to increase both parent and youth fruit and vegetable (F&V) intake. The session lasted 45-60 minutes and included three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…Eleven papers reporting on eight studies evaluating the effectiveness of websites (n = 7) [28][29][30][31][32][33][34][35][36] and apps (n = 1) [37,38] as health promotion tools targeting parents to improve children's nutrition and/or prevent obesity were included ( Table 1). Studies were conducted in the USA [28,30,[32][33][34]36], Sweden [37,38], Australia [31], Switzerland [35] and Belgium [29]. Studies targeted parents of children across a range of developmental stages from young children aged 1-5 years [28] to early adolescence [36].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven papers reporting on eight studies evaluating the effectiveness of websites (n = 7) [28][29][30][31][32][33][34][35][36] and apps (n = 1) [37,38] as health promotion tools targeting parents to improve children's nutrition and/or prevent obesity were included ( Table 1). Studies were conducted in the USA [28,30,[32][33][34]36], Sweden [37,38], Australia [31], Switzerland [35] and Belgium [29]. Studies targeted parents of children across a range of developmental stages from young children aged 1-5 years [28] to early adolescence [36].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Studies were conducted in the USA [28,30,[32][33][34]36], Sweden [37,38], Australia [31], Switzerland [35] and Belgium [29]. Studies targeted parents of children across a range of developmental stages from young children aged 1-5 years [28] to early adolescence [36]. Of included studies, four were randomised controlled trials (RCT), comparing the digital intervention against a healthy eating pamphlet [37,38], healthy eating information delivered online [32][33][34], additional information provided by short message service (SMS) or email [35], or an in-person group education [28].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, few randomized controlled trials have specifically targeted underserved adolescents (Kitzman-Ulrich, et al, 2011; Wilfley, et al, 2007; Wilson, 2009; Wilson, Alia, Kitzman-Ulrich, & Resnicow, 2013), and those that have, demonstrated only marginal or no effects on weight loss (Barr-Anderson, Adams-Wynn, DiSantis, & Kumanyika, 2013; Whitlock, Williams, Gold, Smith, & Shipman, 2005). Furthermore, attrition rates are higher among underserved populations with previous reviews reporting attrition rates as high as 70% among minority populations in comparison to an average range of 12-18% among non-minority youth (Budd, et al, 2007; Jelalian, et al, 2008; White, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that interventions which integrate parenting, motivational and behavioral constructs and address cultural issues are likely to have greater success in producing weight loss outcomes for youth (Barr-Anderson, et al, 2013; Kitzman-Ulrich, et al, 2011; Kitzman-Ulrich, et al, 2010; Kitzmann, et al, 2010; Whitlock, et al, 2005; Wilson, 2009; Wilson, et al, 2013). Notably, a preliminary study to the FIT trial demonstrated the feasibility of integrating motivational and parenting components in the context of weight loss program for overweight African American and Caucasian adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…54 A preliminary study by our group that evaluated a similar on-line web-based program was rated as well-liked and easy to use by African American parents. 55 Thus the proposed study design is unique in that will allow us to test both the effects of the group motivational plus family weight loss (M+FWL) curriculum (compared to a comprehensive health education program; CHE) and the added dose effects of the tailored on-line intervention component on reducing z-BMI in overweight African American adolescents and their parents. After the group session, participants will be re-randomized to either an 8-week on-line intervention or control on-line program resulting in a 2 (M+FWL vs. CHE group) × 2 (intervention vs. control on-line program) factorial design.…”
Section: Introduction To the Rationale For The Fit Trialmentioning
confidence: 99%